Efektivitas Pemasaran Ikan Hias Clownfish (Amphiprion Ocellaris) di PT Agung Aquatic Marine, Badung – Bali - Mutiara Azizah; Yusri Muhammad Yusuf; Ratnawati Ratnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The ornamental fish business is experiencing quite rapid development and has promising economic prospects. Ornamental fish is one of the fishery commodities that has the potential to become an export commodity because ornamental fish originating from Indonesia are in great demand by the international market. The development of the ornamental fish market is increasing but is not followed by a sufficient number of ornamental fish breeders and the lack of regulation of marine ornamental fish exporters in Indonesia, can trigger exporters to over-exploit natural ornamental fish to meet the needs of the ornamental fish market which can result in several species of marine ornamental fish It is threatened with extinction and causes the destruction of coral reefs because several types of coral reefs have direct symbiosis with fish. This research uses qualitative research methods or field research depending on what happens in the field, in this case PT Agung Aquatic Marine. The data analysis used is qualitative descriptive data analysis with data collection techniques through observation, interviews and documentation. Based on sales data for ornamental Clownfish (Amphiprion Ocellaris) from 2022 to 2023, sales show that sales continue to increase. Meanwhile, Clownfish (Amphiprion Ocellaris) which experienced a decrease in orders from customers include Clownfish (Amphiprion Ocellaris) with size (S). This could be caused by the quality of the fish not matching the customer's taste. However, there are also Clownfish (Amphiprion Ocellaris) whose orders continue to increase every month, such as Clownfish (Amphiprion Ocellaris) with size (M) and Black Clownfish (Amphiprion Ocellaris). This is because these ornamental fish have good quality according to customer tastes. Direct marketing of Clownfish ornamental fish (Amphiprion Ocellaris) at PT Agung Aquatic Marine can be said to be effective because it has been able to achieve sales targets and company goals that have been previously set.